2020
DOI: 10.1029/2019jg005051
|View full text |Cite
|
Sign up to set email alerts
|

Varying Contributions of Drivers to the Relationship Between Canopy Photosynthesis and Far‐Red Sun‐Induced Fluorescence for Two Maize Sites at Different Temporal Scales

Abstract: Sun‐induced fluorescence (SIF) has been found to be strongly correlated with gross primary production (GPP) in a quasi‐linear pattern at the scales beyond leaves. However, the causes of the GPP:SIF relationship deviating from a linear pattern remain unclear. In the current study conducted at two maize sites in Nebraska in 2017 summer growing season, we investigated the relationship between GPP and SIF at 760 nm (F760) at two temporal scales and quantified the contributions of incoming photosynthetically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…The high correlation between SIF yield and LUE from our result demonstrates that the SIF response to LUE can be greater than to APAR (Figures 2 and 3). This result itself may seem to contradict the previous findings from continuous crop SIF measurements where APAR explained the majority of the SIF variability (Miao et al, 2018(Miao et al, , 2020Yang et al, 2018) However, our result represents different variability from what was observed in earlier studies, given we measured SIF under relatively invariant solar radiation and under considerable variation of stress-induced photosynthetic depression. Largely invariable incident PAR resulted in much less APAR dependency in both SIF and GPP, and a sufficient variation in photosynthetic depression due to the experimental treatments amplified physiological information and its impact on SIF.…”
Section: Sif Yield Dominantly Explains the Coupling Of Sif And Gpp And The Variability Of Sifcontrasting
confidence: 99%
See 3 more Smart Citations
“…The high correlation between SIF yield and LUE from our result demonstrates that the SIF response to LUE can be greater than to APAR (Figures 2 and 3). This result itself may seem to contradict the previous findings from continuous crop SIF measurements where APAR explained the majority of the SIF variability (Miao et al, 2018(Miao et al, , 2020Yang et al, 2018) However, our result represents different variability from what was observed in earlier studies, given we measured SIF under relatively invariant solar radiation and under considerable variation of stress-induced photosynthetic depression. Largely invariable incident PAR resulted in much less APAR dependency in both SIF and GPP, and a sufficient variation in photosynthetic depression due to the experimental treatments amplified physiological information and its impact on SIF.…”
Section: Sif Yield Dominantly Explains the Coupling Of Sif And Gpp And The Variability Of Sifcontrasting
confidence: 99%
“…However, each measurement point represents the whole canopy response, which integrates leaf‐level responses over the area of 1 m 2 through the vertical layers of the canopy. This approach allowed us to more closely match the SIF and GPP measurement footprint, which has been a limitation in other SIF–GPP studies (Miao et al, 2018, 2020; Yang et al, ,2015, 2018)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MODIS AOD was used to estimate the aerosol conditions in the NCP. Solar‐induced chlorophyll fluorescence (SIF), which has been suggested to be a direct proxy of ecosystem photosynthesis, especially for heavily managed agricultural ecosystems, was used to approximate ecosystem photosynthetic activity of the croplands (Guanter et al., 2014; Miao et al., 2018, 2020; Sun et al., 2017). We used the new long‐term GOME‐2A SIF data set with SIFTER v2 algorithm, which corrected the instrument degradation of GOME‐2A satellite (Kooreman et al., ; van Schaik et al., 2020).…”
Section: Methodsmentioning
confidence: 99%